2016
DOI: 10.1055/s-0036-1572415
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Comparison for Radial and Horizontal Tears

Abstract: Tears in posterior horn of medial meniscus mainly included horizontal tear, transversal tear, radial tear, complex tear, and bucket handle tear. We analyzed and compared the risk factors for radial tear and horizontal tear in the posterior horn of medial meniscus. A total of 407 consecutive cases who received arthroscopic treatment of medial meniscus tears were analyzed retrospectively. Among them, 103 cases were radial tear in posterior horn of medial meniscus and 107 were horizontal tear. Clinical data recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…33 Nevertheless, given the overall result of the between-group comparison including the VLT group, it could be suggested that the patients with greater PTS would be relatively vulnerable to a knee injury and more likely to have a trauma-related lesion, as in the relationship between the PTS and ACL injury. 28,31 Other between-subgroup comparisons did not show a significant difference in the PTS, consistent with the study by Wu et al 32 comparing the radial tear and horizontal tear in the MMPH and the study by Barber et al 4 comparing complex medial meniscal tears and other types of medial meniscal tear. The results of the present study are significant in that we compared not only among types of degenerative tear but also included patients without meniscal tear in a strictly controlled state.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…33 Nevertheless, given the overall result of the between-group comparison including the VLT group, it could be suggested that the patients with greater PTS would be relatively vulnerable to a knee injury and more likely to have a trauma-related lesion, as in the relationship between the PTS and ACL injury. 28,31 Other between-subgroup comparisons did not show a significant difference in the PTS, consistent with the study by Wu et al 32 comparing the radial tear and horizontal tear in the MMPH and the study by Barber et al 4 comparing complex medial meniscal tears and other types of medial meniscal tear. The results of the present study are significant in that we compared not only among types of degenerative tear but also included patients without meniscal tear in a strictly controlled state.…”
Section: Discussionsupporting
confidence: 84%
“…There were also 2 studies that investigated the association between the PTS and meniscal tear patterns but did not compare with those without meniscal tear. 4,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Досить часто такі розриви локалізуються на межі тіла та заднього рогу. Згідно з дослідженнями, радіальні розриви зустрічаються у чоловіків у віці 11-20 років та у жінок 51-70 років [22,23]. Як правило, такі розриви виникають внаслідок травми.…”
Section: показання для реконструктивних операцій на меніскахunclassified
“…The population-based cohort study found that the age is a major risk factor for meniscus tearing, especially in people over 40 years old [6,7]. Previous studies have shown that aging could cause compositional changes in the meniscus, which includes degeneration of collagens, cells, and proteoglycans [8,9].…”
Section: Introductionmentioning
confidence: 99%